A Study on Standard of Living Index (SLI) and its Influence on Rural Area Self-Poisoning Practices, Knowledge of First AID and Prevailing Traditional Practices in Rural Area of Hassan District, Karnataka (Cross-Sectional Study) (Indian Journal of Public Health Research & Development, 2021)
Suicide by pesticide poisoning consumption among young and old is preventable. More so in India, sincelarger population are involved in agriculture and its rampant usage for their cultivation. Also, due to weakerIndia’s public health infrastructure and prevailing folk medicine practices, makes all the more difficult tosave victims and it seems add in to huge burden.Objectives: To estimate pattern of self-poisoning, first AID usage and folk medicine practices influencedby their standard of living.Method: Four primary health centre (PHCs) villages of Hassan taluk were selected by simple randomsampling and every fifth houses were considered as study subjects (159). To assess their socio-economicsituation, standard of living index (SLI) comprising of their basic amenities was adopted to understand itsinfluence on self-poisoning practices.Results: The mean age of males were 44.23 (95 % CI 39.53 to 48.94) with SD (17.57) and females were37.40 (95% CI 34.78 to 40.02) with SD (13.41). Traditional medicine (folk medicine) (125/78.6%) waspracticing for their immediate self-harm (poison) relief. More than 98% respondents told that they do nothave any idea or training towards first AID. 23% in higher living index said victim must be put on theirback (p
Keywords: Self-harm, pesticide poisoning, first AID, Standard of living index (SLI)